Strengthening critical thinking based on the scientific method in second grade students. - Sierra Villamil, Nathalia Lizeth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The development of critical thinking is considered relevant, since it is catalogued as a competence that should be incorporated in the educational system as a soft skill in order to form critical children, likewise a child from the first educational levels requires to ask, explore and share what they know. In the research project, the strengthening of critical thinking from the scientific method in students of the second grade three of the I.E Técnico Comercial “Sagrado Corazón de Jesús” of the municipality of Chiquinquirá was proposed, taking into account the theoretical contributions of those who affirm that the skills of critical thinking are considered as cognitive mechanisms that facilitate the interpretation and selection of information with the purpose of making decisions and proposing hypotheses.